TiO2 Nanotubes Supported PtOx Nanoclusters with Enhanced Mass Activity for Electrocatalytic Hydrogen Evolution. Issue 21 (2nd September 2020) - AlAqad, Khaled M.; Kandiel, Tarek A.; Basheer, Chanbasha
Abstract: Developing proper supports to enhance Pt mass activity is crucial for the practical application of electrocatalytic hydrogen evolution reaction (HER). Herein, TiO2 nanotubes (TNTs) support is fabricated via anodizing Ti foil and loaded with PtOx nanoclusters using a facile photo‐deposition method. The formation of PtOx was confirmed by X‐ray photoelectron spectroscopy analysis. Interestingly, the TNTs supported PtOx (Ti/TNTs/PtOx ) electrocatalyst showed superior activity towards HER than the benchmark Pt/C and TiO2 nanoparticles (TNPs) supported PtOx electrocatalysts. An overpotential of −30 mV was sufficient to deliver −10 mA cm −2 from the acidic medium. The electrocatalytic mass activity of Ti/TNTs/PtOx (i. e. 204 mA mg −1 ) is enhanced by 12 and 1.7‐fold in comparison with those of Pt/C and TNPs supported PtOx electrocatalysts, respectively. The superior activity of Ti/TNTs/PtOx is mainly due to its large electrochemical active surface area and the excellent electron mobility in TNTs support. Abstract : TiO2 Nanotubes (TNTs) : TNTs showed high potential for being applied as a unique support for PtOx nanoclusters in electrocatalytic hydrogen evolution reaction. TNTs supported PtOx electrocatalyst exhibits higher mass activity and lower overpotential than the benchmark Pt/C and TiO2 nanoparticles (TNPs) supported PtOx electrocatalysts. This is mainly due to the high surface area and excellent electron mobility for TNTs in addition to the good interaction between PtOx and TNTs and the high surface area of PtOx active sites.